Careworkers’ lived experiences and their perception of the program for learners with severe to proffound intellectual disabilities - Diale, Galetshetse Vallery (My University, 2022)
Background:The children with severe to profound intellectual disabilities(SPID) had no access to education facilities, as they were referred to as uneducable, a discrepancy with the South African constitution and bill of rights that led the Western Cape Forum for Disabled people to take the Department of Basic Education (DBE) to court. In response to a court order, the DBE introduced the learning program for children with SPID to capacitate the careworkers to offer a formal and funded education to these children. It is unknown whether the program meets the expectations of the careworkers and how they perceive and experience this newly introduced program. Aim of study: To explore the perceptions of careworkers in stimulation care centres of Nkangala District in Mpumalanga province about the learning program and the training provided by the education outreach team. Methodology: A qualitative research method following a descriptive explorative design was applied. Twelve research participants were purposefully selected and engaged in one-on-one in-depth interviews. The data were thematically analysed, using open coding. Findings: The careworkers in Nkangala District of Mpumalanga province appreciate the learning program of LSPD for affording the children who have barriers to access education facilities an opportunity for them to be trained by a multidisciplinary rehabilitation team and education specialists to offer comprehensive intervention to the children in their care. The careworkers shared their lived experiences of how they started and grew over the years in their services and also appreciate the learning program for SPID for sharpening their skills and capacitating them to carry out their duties. On the negative side, the careworkers feel side-lined and undermined based on their level of education as the DBE did not seek their collaboration in major decision making of the program and they do not get remuneration for the additional set of responsibilities and duties emanating from the learning program for LSPID.
A dissertation submitted in fulfillment of the requirements for the degree of Master of Science in Occupational Therapy to the Faculty of Health Sciences, School of Therapeutic Sciences, University of the Witwatersrand, 2022